Genetic drift and mutational hazard in the evolution of salamander genomic gigantism. (1st December 2016) - Mohlhenrich, Erik Roger; Mueller, Rachel Lockridge
Abstract: Salamanders have the largest nuclear genomes among tetrapods and, excepting lungfishes, among vertebrates as a whole. Lynch and Conery (2003) have proposed the mutational‐hazard hypothesis to explain variation in genome size and complexity. Under this hypothesis, noncoding DNA imposes a selective cost by increasing the target for degenerative mutations (i.e., the mutational hazard). Expansion of noncoding DNA, and thus genome size, is driven by increased levels of genetic drift and/or decreased mutation rates; the former determines the efficiency with which purifying selection can remove excess DNA, whereas the latter determines the level of mutational hazard. Here, we test the hypothesis that salamanders have experienced stronger long‐term, persistent genetic drift than frogs, a related clade with more typically sized vertebrate genomes. To test this hypothesis, we compared dN/dS and Kr/Kc values of protein‐coding genes between these clades. Our results do not support this hypothesis; we find that salamanders have not experienced stronger genetic drift than frogs. Additionally, we find evidence consistent with a lower nucleotide substitution rate in salamanders. This result, along with previous work showing lower rates of small deletion and ectopic recombination in salamanders, suggests that a lower mutational hazard may contribute to genomic gigantism in this clade.